LANDASAN EPISTEMOLOGI KOMUNIKASI ISLAM - Hasnun Jauhari Ritonga (State Islamic University North Sumatra, 2008)
Abstract: Epistemological Foundations of Islamic Communication. Epistemology is a branch of philosophy which is inherent in the superstructureof knowledge. Epistemology discusses the process of acquiring knowledge, scientific sources, validity of theoretical framework of sciences, and scientific streams. Like other Islamic sciences, Islamic communication science derives from al-Qur’an and Hadist as the main sources. Analyzing the universe, human being, historical records of men are the subjects of the Islamic communication science. The present paper intends to elaborate broadly the scopes of the science, and describe critically the values leading to emerge it.Kata Kunci: epistemologi, komunikasi Islam, kerangka keilmuan